Macroeconomic Impact of Maternity (Parental) Leave Comparing the Czech Republic with Brazil - Kalkusová, Marie; De Castro, Tereza; Neumann, Pavel, 1956-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
This thesis aims to estimate the macroeconomic impact of maternity and parental/paternal leave in the Czech Republic and Brazil. In addition, the thesis stresses out the costs of Czech model application to Brazil and vice-versa. The first chapter brings a theoretical framework. It compares the analyzed policies in both countries and introduces the relevant terms. The second chapter estimates the costs of maternity and parental/paternal leave related to public expenditure and GDP for the years 2005-2014 and brings own simulation model for Czech model application to Brazil and vice-versa. The third chapter analyses the inefficiencies and suggest possible mitigation. The results show the costs of 0.71% of GDP and 1.66% of public expenditure in the Czech Republic and 0.50% GDP and 2.27% of public expenditure in Brazil in 2014. The Czech model applied in Brazil would be very costly and the opposite scenario would lead to the decrease of macroeconomic burden in the Czech Republic. The thesis also analyzes the influence of maternal and parental leave in other areas, such as labor market, where the current structure may penalize Czech women in long term. By this analysis, the thesis contributes to the current debate about the impact, the length and costs of maternity and parental leave.
Vedoucí práce: Tereza De Castro
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses